Corticotrophin-Releasing Factor, Related Peptides, and Receptors in the Normal and Inflamed Gastrointestinal Tract - Buckinx, Roeland; Adriaensen, Dirk; Van Nassauw, Luc; Timmermans, Jean-Pierre (Frontiers in Neuroscience, 2011)
Corticoptrophin-releasing factor (CRF) is mainly known for its role in the stress response in the hypothalamic-pituitary-adrenal axis. However, increasing evidence has revealed that CRF receptor signaling has additional peripheral effects. For instance, activation of CRF receptors in the gastrointestinal tract influences intestinal permeability and motility. These receptors, CRF1 and CRF2, do not only bind CRF, but are also activated by urocortins. Most interestingly, CRF-related signaling also assumes an important role in inflammatory bowel diseases in that it influences inflammatory processes, such as cytokine secretion and immune cell activation. These effects are characterized by an often contrasting function of CRF1 and CRF2. We will review the current data on the expression of CRF and related peptides in the different regions of the gastrointestinal tract, both in normal and inflamed conditions. We next discuss the possible functional roles of CRF signaling in inflammation. The available data clearly indicate that CRF signaling significantly influences inflammatory processes although there are important species and inflammation model differences. Although further research is necessary to elucidate this apparently delicately balanced system, it can be concluded that CRF-related peptides and receptors are (certainly) important candidates in the modulation of gastrointestinal inflammation.